Family structure, early motherhood, child outcomes and well-being: evidence from South Africa - Anakpo, Godfred (My University, 2020)
Family structure, early motherhood and child outcomes are cardinal social factors with potential effects on overall well-being, later life outcomes and inter-generational development. However, the existing literature has failed to fully explore these areas. This study therefore uses National Income Dynamic survey data on households, adults and children collected in 2 years interval from 2008-2014 in South Africa to investigate three main research questions: (1) How does family structure affect household well-being? (2) What are the effects of early motherhood on the later life outcomes of the mothers? And (3) How does early motherhood affect child outcomes? These three research questions set forth the direction of this study in three stages, each seeking to address the research question raised. Family structure may be related to household’s well-being; therefore, the first paper uses OLS regression, fixed effect and dynamic panel analysis techniques (System GMM) to examine the impact of family structure on household well-being in South Africa. Findings emanating from this study show that intact married households have significant positive relationship with household reported well-being, while the relationship of cohabiting with household reported well-being and subjective well-being is positively significant. Furthermore, extended households, households headed by females and grandparents, have significant negative relationship with household income and consumption, Lastly, while grandparent headed household has positive relationship with household reported well-being, bigger household size significantly decrease household reported well-being. The pathway to motherhood and its later life outcomes have received considerable attention in both research and political agenda due to its fundamental and pivotal link to life-course and inter-generational development of mothers and their progenies. This paper uses National Income Dynamic survey data on mothers collected in 2 years interval from 2008-2014 in South Africa to examine the impacts of teen motherhood on mothers’ later life outcomes using propensity score with different matching algorithms. The study reveals from most matching techniques that teen motherhood has significant negative effects on women’s educational attainment, economic well-being, psychological well-being and life satisfaction. Additionally, the outcome on health is adverse only in underweight category while high perceived health and less obesity are associated with teen motherhood. The previous paper on early motherhood documented that very few studies exist ion the implications of early motherhood but focused mainly on the effects on mothers. The existing works on the impacts of early motherhood on children are either limited to childbirth weight or are descriptive in nature with very limited findings on other areas of child outcomes. Therefore, the third paper examines the effects of early motherhood on child outcomes, especially on child’s education, economic well-being, education, perceived health and birth weight using propensity weighted logistic regression. Findings from this study thus reveal that teen motherhood significantly increases child grade repetition and economic dependency. The effect on economic dependency however, became insignificant after controlling background precursors such as household income and parental marital status, family types and head composition of the household to which the child belongs. Furthermore, teen motherhood association with child health perceived health is significantly positive but insignificant for birth weight. The findings from this study have policy implications and directions. The implications for policy of family structure stresses the importance of gender tailored policy (for instance for female headed household), built appropriate and adequate systems of support for healthy development and economic empowerment policy especially for disadvantaged families and households. Furthermore, proactive, reactive and post-active policy interventions, which require the complementary role of policymakers, government, parents, service providers and adolescents are recommended for mothers’ later life and child outcomes of early motherhood. This policy needs to ensure that services and rights related to sex education and reproductive health are addressed in schools. Policy on family involvement strategies, childcare and regular health programmes such as job training to young and teenage mothers and returning to school after delivery are recommended. Additional training, capacity building and job counseling to young mothers are also highlighted
A thesis submitted to the School of Economics & Finance, Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy in Economics, 2020